RECENT APPROACHES IN GLUCOSE RESPONSIVE INSULIN DELIVERY SYSTEM - SHARMA, SAURABH; KASHYAP, ASHUTOSH; BISWAL, PRASANTA KUMAR; DAS, SURYA NARAYAN (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Diabetes mellitus is a chronic medical condition currently affecting 382 million people across the globe, caused due to increased blood glucose levels due to less insulin production or insulin resistance. Subcutaneous insulin administration for diabetes is the only most accepted therapy for maintaining blood glucose levels in diabetic patients. Many patients with advanced type II diabetes mellitus need to regularly monitor their blood glucose level to keep their blood glucose level in the target range. However long-term insulin therapy through an invasive route of administration causes problems with patient compliance and a sudden decrease in blood glucose levels. An artificial closed-loop insulin release system that mimics the glucose-responsive insulin secretion by β-cells of pancreas is one of the ways to overcome the problem faced with the conventional method of insulin administration. Many polymeric formulations showed an improved glucose-responsive release of insulin when incorporated with glucose-responsive catalysts such as glucose oxidase, phenylboronic acid, and glucose binding proteins, the release rate can be controlled by optimizing the concentration of glucose-responsive catalysts. This article is been focused on different mechanisms of glucose-responsive release by incorporation with glucose-responsive catalysts.